Approach to Acute Headache: A Flipped Classroom Module for Emergency Medicine Trainees - Jeff Riddell; Stacy Sawtelle; Paul Jhun; James Comes; Ramin Tabatabai; Daniel Joseph; Jan Shoenberger; Esther Chen; Christopher Fee; Stuart Swadron (eScholarship Publishing, University of California, 2016)
Audience: This module is designed for emergency medicine trainees. Though it focuses on those early in their career (medical students and junior residents), it is applicable to all emergency medicine learners. Introduction: In the United States, headache is the fifth most-common primary complaint of patients presenting to the emergency department and can be the primary symptomatic manifestation of many life-threatening illnesses. The emergency physician plays a unique role in diagnosing and managing these patients. The emergency physician's two major responsibilities are to relieve headache pain and to ensure that life-threatening causes are diagnosed and treated. Objectives: At the end of this module, the learner will be able to: 1) list the diagnoses critical to the emergency physician that may present with headache; 2) identify key historical and examination findings that help differentiate primary (benign) from secondary (serious) causes of headache; 3) discuss the indications for diagnostic imaging, lumbar puncture and laboratory testing in patients with headache; 4) recognize life-threatening diagnoses on CT imaging and CSF examination; 5) describe treatment strategies to relieve headache symptoms. Methods: This module includes a complete flipped classroom module. Learners are responsible for viewing a 20-minute video prior to the 30-minute small-group, case-based didactic discussion portion. The learners are assessed with multiple-choice question assessments, for low stakes retrieval practice or spaced practice. This could alternatively be run as a team-based learning session, with the pre- and post-tests used as an individual or group readiness assessment test, and the small group exercises converted to a group application exercise.